Serra da Estrela : an approach to the territory, its potential and future for the winter tourism industry - Garcia, Raul Ressano (2011)
This paper aims to explore the territory of “Serra da Estrela”, in the North of Portugal, bearing in mind some studies previously undertaken about tourism in the area, mainly focusing on snow tourism. Being snow tourism essentially connected with sports tourism the approach and methodology followed in this article is a sport related one. The literature review which was undergone raised some questions to which answers were sometimes hard to find. Nevertheless, after analyzing some published surveys and getting acquainted with the region, the article provides answers or leads to matters such as: temperature related issues, artificial snow production, renewal of infrastructures, and others. The aim of this article is to initiate a first approach to the territory, get to know its main problems and analyse some proposals to solve some of the latter as suggested by some of the analysed case studies. Personal experience from 35 years of practical experience in winter sports is also provided.